Integrated Measurement System Of Postural Angle And Electromyography Signal For Manual Materials Handling Assessment - Saptari, Adi; Halim, Isa; Abulais, Mohd Fairil; Padmanathan, Vinothini (UTHM Publisher, 2021)
Improper design of manual materials handling (MMH) tasks at workplace can cause musculoskeletal disorders such as muscle strain to industrial workers. To avoid these disorders, ergonomists and engineers require an integrated measurement system which allows them to study the interaction of body posture and muscle effort during performing MMH tasks. However, far too little attention has been paid to develop an integrated measurement system of body posture and muscle activity for assessing MMH tasks. The aim of this study was to develop and test a prototype of integrated system for measuring postural angles and electromyography (EMG) signals of a worker who doing MMH tasks. The Microsoft Visual Studio software, a 3D camera (Microsoft Kinect), Advancer Technologies muscle sensors and a microcontroller (NI DAQ USB-6000) were applied to develop the integrated postural angle and EMG signal measurement system. Additionally, a graphical user interface was created in the system to enable users to perform body posture and muscle effort assessment simultaneously. Based on the testing results, this study concluded that the patterns of EMG signals are depending on the postural angles which consistent with the findings of established works. Further study is required to enhance the validity, reliability and usability of the prototype so that it may facilitate ergonomists and engineers to assess work posture and muscle activity during MMH task.